Bothrops (Fer-de-lance) snakebites in the French departments of the Americas (Martinique and Guyana): Clinical and experimental studies and treatment by immunotherapy - Dabor Resiere; Hatem Kallel; Jonathan Florentin; Stephanie Houcke; Hossein Mehdaoui; José María Gutiérrez; Remi Neviere (Public Library of Science (PLoS), 2023)
Snakebite envenomation is a relevant medical hazard in French Guiana and Martinique, two French territories in the Americas. All snakebite envenomations in Martinique are inflicted by the endemic viperid species Bothrops lanceolatus, whereas Bothrops atrox is responsible for the majority of snakebites in French Guiana, although other venomous snake species also occur in this South American territory. This review summarizes some of the key aspects of the natural history of these species, as well as of their venom composition, the main clinical manifestations of envenomations, and their treatment by antivenoms. B. atrox venom induces the typical set of clinical manifestations characteristic of Bothrops sp. venoms, i.e., local tissue damage and systemic alterations associated with coagulopathies, hemorrhage, hemodynamic alterations, and acute kidney injury. In the case of B. lanceolatus venom, in addition to some typical features of bothropic envenomation, a unique and severe thrombotic effect occurs in some patients. The pathogenesis of this effect remains unknown but may be related to the action of venom components and inflammatory mediators on endothelial cells in the vasculature. A monospecific antivenom has been successfully used in Martinique to treat envenomations by B. lanceolatus. In the case of French Guiana, a polyvalent antivenom has been used for some years, but it is necessary to assess the preclinical and clinical efficacy against viperid venoms in this country of other antivenoms manufactured in the Americas.